2018
DOI: 10.1002/ab.21747
|View full text |Cite
|
Sign up to set email alerts
|

The role of aggression‐related early maladaptive schemas and schema modes in aggression in a prisoner sample

Abstract: Contemporary social-cognitive aggression theory and extant empirical research highlights the relationship between certain Early Maladaptive Schemas (EMSs) and aggression in offenders. To date, the related construct of schema modes, which presents a comprehensive and integrated schema unit, has received scant empirical attention. Furthermore, EMSs and schema modes have yet to be examined concurrently with respect to aggressive behavior. This study examined associations between EMSs, schema modes, and aggression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 42 publications
2
33
0
9
Order By: Relevance
“…This formula accounts for dependence between effect sizes when averaging scores that are correlated with one another based on the sample size and estimated correlation between constructs or subscales. To estimate the correlation between individual EMS scores and domains for the present study, the correlations between individual EMS scores and domains were extracted from all studies where they were reported (Atkins, 2017; Calvete & Orue, 2010; Calvete, Corral, & Estévez, 2007; Calvete, Fernandez‐Gonzalez, Gonzalez‐Cabrera, & Gamez‐Guadix, 2018a; Campbell, 2002; Carlucci et al, 2018; Clifton, 1994; Dunne, Gilbert, Lee, & Daffern, 2017; Estévez, Ozerinjauregi, & Herrero‐Fernández, 2016; Farr, 2010; Gay et al, 2013; Hassija, Robinson, Silva, & Lewin, 2018; Janovsky, Clark, & Rock, 2019; McKee et al, 2012; Messman‐Moore & Coates, 2007; Mojallal et al, 2015; Munroe, 2014; Shorey et al, 2015; Stiles, 2004; Yoo, Park, & Jun, 2014). Based on the extracted correlations between all available individual EMS scores and domains, the correlations were averaged to produce an estimated correlation between individual EMS scores ( r = .45) and EMS domains ( r = .60) for use in the formula.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This formula accounts for dependence between effect sizes when averaging scores that are correlated with one another based on the sample size and estimated correlation between constructs or subscales. To estimate the correlation between individual EMS scores and domains for the present study, the correlations between individual EMS scores and domains were extracted from all studies where they were reported (Atkins, 2017; Calvete & Orue, 2010; Calvete, Corral, & Estévez, 2007; Calvete, Fernandez‐Gonzalez, Gonzalez‐Cabrera, & Gamez‐Guadix, 2018a; Campbell, 2002; Carlucci et al, 2018; Clifton, 1994; Dunne, Gilbert, Lee, & Daffern, 2017; Estévez, Ozerinjauregi, & Herrero‐Fernández, 2016; Farr, 2010; Gay et al, 2013; Hassija, Robinson, Silva, & Lewin, 2018; Janovsky, Clark, & Rock, 2019; McKee et al, 2012; Messman‐Moore & Coates, 2007; Mojallal et al, 2015; Munroe, 2014; Shorey et al, 2015; Stiles, 2004; Yoo, Park, & Jun, 2014). Based on the extracted correlations between all available individual EMS scores and domains, the correlations were averaged to produce an estimated correlation between individual EMS scores ( r = .45) and EMS domains ( r = .60) for use in the formula.…”
Section: Resultsmentioning
confidence: 99%
“…Approval/recognition seeking and punitiveness failed to reach statistical significance despite having a small to moderate correlation coefficient (Table 3). One explanation for these findings is that EMSs of approval/recognition seeking and punitiveness were only recently added to the YSQ and, as a result, were not measured by the majority of studies included in this meta‐analysis (Braet, Van Vlierberghe, Vandevivere, Theuwis, & Bosmans, 2013; Dunne et al, 2017; Esmaili et al, 2016; Hassija et al, 2018; Messman‐Moore & Coates, 2007; Roelofs, Lee, Ruijten, & Lobbestael, 2011; Thimm, 2013; Yoo et al, 2014). The limited number of studies found that measured EMSs of approval/recognition seeking and punitiveness may have limited the degree of statistical power available to detect significant associations for these particular EMSs and interpersonal problems.…”
Section: Discussionmentioning
confidence: 99%
“…It would thus be of interest to know about the goals the participants thought have been frustrated by the task and that elicited anger. Clinical reports and empirical studies suggest that even minor triggers may activate maladaptive schemata of humiliation, defeat, or rejection and the current frustrating situation might be such a trigger (40). Alternatively, individuals with BPD might experience failure in their social rank motive (39) or experiences failure in the task as an intolerable constraint.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents these schema modes and their associated domains. Keulen-de Vos et al (2016) and Dunne, Gilbert, Lee, and Daffern (2018) suggest that schema modes are important to understanding aggression propensity in forensic populations. In a sample of 95 male patients with antisocial, borderline, narcissistic, or paranoid PDs within seven psychiatric inpatient facilities in the Netherlands, Keulen-de Vos et al (2016) utilized a modified Mode Observation Scale (MOS; Bernstein, de Vos, & Van den Broek, 2009) to identify and record schema mode activation from descriptions of patients' crimes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, modes predictive of institutional violence were Vulnerable-Child, Angry-Child, and the overcompensatory mode domain. Using the Schema Mode Inventory (SMI; Young et al, 2014), to study associations between schema modes and aggression in a sample of 208 adult male prisoners, Dunne, Gilbert, Lee, & Daffern (2018) found that three schema Focuses attention on locating and revealing a perceived threat Source. Adapted from Dunne (2017).…”
Section: Introductionmentioning
confidence: 99%